1,3,4-Thiadiazole: Synthesis, Reactions, and Applications in Medicinal, Agricultural, and Materials Chemistry - Hu, Yang; Li, Cui-Yun; Wang, Xiao-Ming; Yang, Yong-Hua; Zhu, Hai-Liang (Chemical reviews, 2014)
The synthesis, reactions and medicinal applications of the 1,3,4-thiadiazole ring in solution and the solid phase were investigated. The physical and chemical properties of biosostere and the reactions of aromatic and heterocyclic hydrazides with triethyl orthoformate were also explored.